1975
DOI: 10.1136/gut.16.11.866
|View full text |Cite
|
Sign up to set email alerts
|

Viral antibody studies in pancreatic disease.

Abstract: SUMMARY Viral studies were performed on sera from 54 patients with recent acute pancreatitis, 10 with recurrent acute pancreatitis, seven with chronic pancreatitis, and 10 with pancreatic carcinoma, and on sera from 81 age-and sex-matched controls. In 29 of the acute pancreatitis patients from whom paired sera were obtained no convincing evidence of recent viral infection was found. A higher incidence of raised antibody titres against Coxsackie B3 and B4 was observed in the group of acute pancreatitis patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

1977
1977
2000
2000

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…However, we have noted a similar experience to that of other workers (Leinikki et al, 1973;Capner et al, 1975) regarding moderate CF titre rises to Coxsackie B and Mycoplasma pneumoniae occasionally occurring in acute pancreatitis patients. Therefore we support their contentions that a selective anamnestic response may be an accompaniment of acute pancreatitis or that pancreatic antigens (released during acute pancreatitis) may share common determinants with Coxsackie B and mycoplasma pneumoniae antigens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, we have noted a similar experience to that of other workers (Leinikki et al, 1973;Capner et al, 1975) regarding moderate CF titre rises to Coxsackie B and Mycoplasma pneumoniae occasionally occurring in acute pancreatitis patients. Therefore we support their contentions that a selective anamnestic response may be an accompaniment of acute pancreatitis or that pancreatic antigens (released during acute pancreatitis) may share common determinants with Coxsackie B and mycoplasma pneumoniae antigens.…”
Section: Discussionsupporting
confidence: 90%
“…Received for publication 6 August 1976 raised antibody titres to Coxsackie B are present in some patients with pancreatitis but the authors concluded that no case in their series was caused by acute viral infection (Capner et al, 1975). They suggest a selective anamnestic response, or low grade infection, or common determinants between pancreatic and Coxsackie antigens may explain their observations.…”
mentioning
confidence: 92%
“…Puncreatitis. Infection with Coxsackie viruses B3, B4, and B5 has previously been reported in acute pancreatitis (3,4). In this child the high titre of antibodies to Coxsackie B4 supported this diagnosis, although the absence of any early serum sample precluded demonstration of a rising titre.…”
Section: Discussionsupporting
confidence: 58%
“…The viruses most frequently thought to be responsible are mumps virus (Feldstein et al, 1974;Naficy et al, 1973), Coxsackie B virus (Capner et al, 1975;Ursing, 1973;Tsui et al, 1972), Epstein-Barr virus (Wislocki, 1968), and measles virus (Bunnel & Monif, 1972). An association between viral hepatitis and acute pancreatitis has also been observed, although most of the patients concerned had fulminating hepatitis and the causal agent has been identified in only a very few patients (Archod, 1968;Parbhoo et al, 1973;Wands et al, 1973).…”
Section: Introductionmentioning
confidence: 99%